Effect of incorporating finger millet in wheat flour on mixolab behavior, chapatti quality and starch digestibility - Sharma, B.; Gujral, H.; Solah, Vicky (Elsevier BV, 2017)
© 2017 Elsevier LtdWheat and finger millet flour (two cultivars) were blended in the ratio (3:1) to form a composite flour and its dough properties were studied on the mixolab. The chapatti making and digestibility behavior of the composite flour was also investigated. The wheat finger millet (WFM) flour blend displayed up to 30.7% higher total phenolic content (TPC), 38.2% higher total flavonoid content (TFC) and 75.4% higher antioxidant activity (AOA) than the wheat flour. Chapattis prepared from the composite blends exhibited lower retrogradation as evident by the mixolab retrogradation index, higher values of soluble starch and soluble amylose in stored chapatti. The slowly digestible starch (SDS) correlated positively (R = 0.816, p < 0.05) with TPC and water absorption correlated positively (R = 0.995, p < 0.05) with damage starch content. The chapattis made from the composite flour had higher SDS and resistant starch (RS) values demonstrating potential as a food with functional characteristics.